Ocena wpływu czynnika ludzkiego jako bezpośredniej determinanty funkcjonowania obwodowych komisji wyborczych. Praktyczny zarys problematyki - Kamil Krauschar (Acta Iuris Stetinensis, 2021)
The publication presents selected issues of legal determinants of the operation of district electoral commissions and their impact on the election process. In the context of the existing code regulations, it is reasonable to review the events that took place with the participation of members of district electoral commissions in the elections held in 2018–2020 to the bodies of local government units, the Sejm and the Senate of the Republic of Poland, the European Parliament and to the office of the President of the Republic of Poland. The aim of the publication is to obtain an answer to the theses put forward herein: what determinants directly affect the functioning of the election process and what is the impact of the human factor (members of district electoral commissions) on its proper course? Additionally, it should be verified whether the current model of nominating (in fine appointing, resigning, supplementing) members to district electoral commissions requires the legislator’s interference. The analysis of the problems to date sheds light on the scope of the irregularities identified and constitutes a contribution to the introduction of legislative changes to the election law. A comprehensive approach to the topic allows insight into a practical outline of the problems noted in the course of the operation of district electoral commissions.